Improving care for cancer-related and other forms of lymphoedema in low- and middle-income countries: a qualitative study - Eric Torgbenu; Tim Luckett; Mark Buhagiar; Cecilia Mauricio Requena; Jane L. Phillips (BMC, 2022)
Abstract Background Lymphoedema is a common, distressing and debilitating condition that can be related to cancer and its treatment or other conditions. Little is known about current practices in the diagnosis, assessment and management of lymphoedema in low- and middle-income countries (LMIC). Aim To describe current practices in diagnosing, assessing and managing cancer-related and other forms of lymphoedema in LMIC, and related barriers and facilitators. Methods An exploratory-descriptive qualitative study. Participants were lymphoedema experts or health care professionals identified via published lymphoedema papers and professional organizations respectively. Sampling was purposive to ensure a diversity of perspectives and experience. Data collection was via semi-structured telephone/video interviews, and questions canvassed participants' experiences and perceptions of lymphoedema care in LMIC. Interviews were audio-recorded and transcribed verbatim. Analysis proceeded via inductive coding before mapping codes to the World Health Organization's (WHO) Innovative Care for Chronic Conditions Framework. Results Nineteen participants were interviewed, most of whom were physiotherapists (n = 11). Ten participants worked permanently in a LMIC, while the remainder were based in a high-income country (HIC) and had been involved in initiatives to improve lymphoedema care across multiple LMIC. Participants indicated that management of cancer versus non-cancer related lymphoedema was similar, but that pathways to care were more straight-forward for those receiving cancer care, leading to earlier diagnosis. Key facilitators to optimizing lymphoedema care in LMIC included: 1) joining forces to overcome lymphoedema-related stigma; 2) building workforce capabilities; and 3) partnering with patients and families to support self-management. Ideas for building workforce included developing health professional knowledge, supporting a commitment to multidisciplinary team care, and adapting HIC guidelines for lymphoedema care to LMIC. Partnering with patients and families to support self-management involved following the person-centred approach, establishing clear communication, promoting adherence to management, adapting management to available resources, and involving patient family and friends in lymphoedema care. Conclusion Raising community and health professional awareness regarding lymphoedema and its management is a key first step to improving care outcomes. Resources for clinicians and patients/families developed for lymphoedema care in HIC need to be adapted for low resource settings.